2016
DOI: 10.1016/j.exger.2016.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Aging and adipose tissue: potential interventions for diabetes and regenerative medicine

Abstract: Adipose tissue dysfunction occurs with aging and has systemic effects, including peripheral insulin resistance, ectopic lipid deposition, and inflammation. Fundamental aging mechanisms, including cellular senescence and progenitor cell dysfunction, occur in adipose tissue with aging and may serve as potential therapeutic targets in age-related disease. In this review, we examine the role of adipose tissue in healthy individuals and explore how aging leads to adipose tissue dysfunction, redistribution, and chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
228
0
6

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(237 citation statements)
references
References 141 publications
(192 reference statements)
3
228
0
6
Order By: Relevance
“…Some identified exogenous triggers include smoking (Behnia et al, 2016), air pollution (Fougere et al, 2015), persistent infections (Derhovanessian et al, 2011; Oppermann et al, 2012) and overweight or obesity (Giugliano et al, 2006). Several endogenous factors also play a relevant role, including: overproduction of reactive oxygen species (ROS) (Zhang et al, 2016) and advanced glycation end-products (AGEs) (Yamagishi and Matsui, 2016), mitochondrial dysfunction (Lopez-Lluch et al, 2015), renin-angiotensin system (RAS) deregulation (Duprez, 2006), hormonal changes (Epel and Lithgow, 2014; Gubbels Bupp, 2015), visceral adiposity (Palmer and Kirkland, 2016), changes in the gut microbiota (Biagi et al, 2010) and accumulation of cell debris due to a defective autophagy (Franceschi et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Some identified exogenous triggers include smoking (Behnia et al, 2016), air pollution (Fougere et al, 2015), persistent infections (Derhovanessian et al, 2011; Oppermann et al, 2012) and overweight or obesity (Giugliano et al, 2006). Several endogenous factors also play a relevant role, including: overproduction of reactive oxygen species (ROS) (Zhang et al, 2016) and advanced glycation end-products (AGEs) (Yamagishi and Matsui, 2016), mitochondrial dysfunction (Lopez-Lluch et al, 2015), renin-angiotensin system (RAS) deregulation (Duprez, 2006), hormonal changes (Epel and Lithgow, 2014; Gubbels Bupp, 2015), visceral adiposity (Palmer and Kirkland, 2016), changes in the gut microbiota (Biagi et al, 2010) and accumulation of cell debris due to a defective autophagy (Franceschi et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…There are a few 283 reasons to explain the relation between age and MetS. According to Lovre and colleagues [41], aging 284 is accompanied by the decreased in lean mass, which may predispose the individuals to the increased 285 of total fat and insulin resistance that were positively associated with the metabolic dysfunction. As …”
mentioning
confidence: 99%
“…The expression level of PR domain containing 16 (PRDM16), a zinc finger-containing transcription factor is high in mouse BAT compared to visceral WAT [21]. A knock-down of PRDM16 in brown fat cells leads to an increase in white adipose and muscle-specific genes, suggesting that it acts as a key regulator of brown fat cell fate [21], During embryonic development, BAT is known to be one of the earliest fat depots to form [9], Interscapular BAT is the most prominent depot that plays a major role In maintaining infant body temperature during very early years of life and is known to regress progressively with age [22], [23]. Experimental findings from the lineage tracing of adipocytes in vivo have clearly demonstrated that BAT arises from Myf5-expressing (Myf5+) precursors, a key myogenic regulatory factor expressed in committed skeletal muscle precursors [24].…”
Section: Plasticity Biogenesis and Molecular Gene Signature Of Brownmentioning
confidence: 99%
“…Trans-differentiation has also been suggested to allow efficient conversion of white adipocytes to brown adipocytes and vice versa [29], Warm adaptations are also reported to convert beige adipocytes into matured white adipocytes [30]. Similar conversion of beige to white adipocytes has also been speculated to result from aging [23]. In spite of all these recent findings supporting the evidence for trans-differentiation, this hypothesis still needs to be critically analyzed by studying the life-cycle of beige adipocytes.…”
Section: Plasticity Biogenesis and Molecular Gene Signature Of Brownmentioning
confidence: 99%